Effects of magnetic ionic liquid as a lubricant on the friction and wear behavior of a steel-steel sliding contact under elevated temperatures - Jiajia Jia; Guangbin Yang; Chunli Zhang; Shengmao Zhang; Yujuan Zhang; Pingyu Zhang (Friction)
Abstract A magnetic ionic liquid (abridged as MIL) [C6mim]5[Dy(SCN)8] was prepared and used as the magnetic lubricant of a steel-steel sliding pair. The tribological properties of the as-prepared MIL were evaluated with a commercially obtained magnetic fluid lubricant (abridged as MF; the mixture of dioctyl sebacate and Fe3O4, denoted as DIOS-Fe3O4) as a control. The lubrication mechanisms of the two types of magnetic lubricants were discussed in relation to worn surface analyses by SEM-EDS, XPS, and profilometry, as well as measurement of the electric contact resistance of the rubbed steel surfaces. The results revealed that the MIL exhibits better friction-reducing and antiwear performances than the as-received MF under varying test temperatures and loads. This is because the MIL participates in tribochemical reactions during the sliding process, and forms a boundary lubrication film composed of Dy2O3, FeS, FeSO4, nitrogen-containing organics, and thioether on the rubbed disk surface, thereby reducing the friction and wear of the frictional pair. However, the MF is unable to form a lubricating film on the surface of the rubbed steel at 25 °C, though it can form a boundary film consisting of Fe3O4 and a small amount of organics under high temperature. Furthermore, the excessive Fe3O4 particulates that accumulate in the sliding zone may lead to enhanced abrasive wear of the sliding pair.